2020
DOI: 10.1038/s41598-020-63444-3
|View full text |Cite
|
Sign up to set email alerts
|

Stability and anti-proliferative properties of biologically active compounds extracted from Cistus L. after sterilization treatments

Abstract: The growing interest of oncologists in natural compounds such as polyphenols and flavonoids is encouraging the development of innovative and efficient carriers for the delivery of those drugs. This study examines carboxymethyl chitosan-based microcapsules created by spray drying as a method for delivering biologically active compounds isolated from the Cistus herb. Effects of sterilization and encapsulation on the polyphenol and flavonoid content of Cistus extract were investigated to optimize the production p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Since ancient times, Cistaceae have been used in ethnomedicine due to their pharmacological potential against a broad range of disorders, including various skin diseases, diarrhea, ulcers, dysentery, catarrh, menstruation difficulties, and gout due to a number of natural pharmacological compounds they consist of [ 2 , 3 , 4 ]. According to ethno-pharmacology, the Cistus species has been used due to its antimicrobial, antiproliferative, anticancer, antiviral, antioxidant, anti-inflammatory, antiulcerogenic, antidiarrheal, and antispasmodic activity [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. It is also known that some Cistus species have been used in human and animal diets, such as goats, lamb and beef [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since ancient times, Cistaceae have been used in ethnomedicine due to their pharmacological potential against a broad range of disorders, including various skin diseases, diarrhea, ulcers, dysentery, catarrh, menstruation difficulties, and gout due to a number of natural pharmacological compounds they consist of [ 2 , 3 , 4 ]. According to ethno-pharmacology, the Cistus species has been used due to its antimicrobial, antiproliferative, anticancer, antiviral, antioxidant, anti-inflammatory, antiulcerogenic, antidiarrheal, and antispasmodic activity [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. It is also known that some Cistus species have been used in human and animal diets, such as goats, lamb and beef [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…As observed in Figure 2 , there has been an exponential increase of research and publications related to the possible use of polyphenolic compounds in cancer therapy [ 15 ]. The fact that polyphenols can be extracted using simple and green techniques—such as ultrasound-assisted extraction, and that after being sterilized, polyphenols preserve most of their properties intact—will contribute to the study of these compounds as potential anticancer drugs [ 16 , 17 ].…”
Section: Polyphenolsmentioning
confidence: 99%
“…They are widely contained in plants and can be classified into the following groups: phenolic acids, flavonoids, lignans, curcuminoids, stilbenes, and tannins [ 4 ]. Their pattern and substitution degrees determine a broad spectrum of biological properties such as free radical scavenging, metal-chelating, antimicrobial, immunostimulating, wound-healing and chemopreventive activities [ 5 , 6 , 7 , 8 , 9 ]. For instance, their natural antioxidant activity is able to inhibit oxidative chain reactions in human skin and can therefore prevent some skin diseases, premature ageing and skin damage, including wounds and burns [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…They contain gallic acid, rutin, different flavonoid aglycones, and flavan-3-ols, as well as catechin, epicatechin, gallocatechin, gallocatechin-3-gallate and oligomeric procyanidin B1 and B3 as Biologically Active Compounds (BACs) [ 8 ]. In a previous paper, we showed that BAC content and activity are preserved when a steam sterilization process is employed, thus expanding the application opportunities in Medicine for these natural compounds [ 9 ].…”
Section: Introductionmentioning
confidence: 99%